Connie L. Scarborough, Viewing Disability in Medieval Spanish Texts. Disgraced or Graced - Daniel Gutiérrez Trápaga (Medievalia, 2019)
Connie L. Scarborough, Viewing Disability in Medieval Spanish Texts. Disgraced or Graced, Amsterdam: Amsterdam University Press, 2018, 229 pp. (Premodern Health, Disease, and Disability, 1).